Effect of extraction conditions on protein concentration during edible bird’s nest alkaline hydrolysis - Nurul Ain, Jumri (2014)
Edible bird’s nest (EBN) is originated from the saliva of swiftlet. There are four species of swiftlet which are Collocalia fuciphaga, Collocalia germanis, Collocalia maxima and Collocalia unicolor. Collocalia fuciphaga is the common species which can be found in Malaysia. EBN consists mainly of amino acids, carbohydrates and mineral salts but it major ingredients were protein. Protein from EBN can be extracted by water, acid, alkaline and enzymatic hydrolysis method. This study focused on alkaline hydrolysis using sodium hydroxide (NaOH) at 50°C. Prior to alkaline hydrolysis, pre-treatment method (EBN cleaning by soaked with water, feathers removal and fine plumage from EBN sample) has been carried out. The effect of extraction time, NaOH concentration and liquid solid ratio (LSR) on protein concentration have been determined during alkaline hydrolysis. The optimum condition of alkaline hydrolysis has been identified using response surface methodology (RSM). From the experimental result, it showed that the maximum protein concentration was at 25 minutes of extraction time, 30:1 of LSR and 100 g/L NaOH concentration. However, increased in LSR and NaOH concentration were increased the protein concentration. The optimum condition of protein concentration was 1.260 g/L during alkaline hydrolysis using RSM were found at 25 minutes of extraction time, 100g/L NaOH concentration and 30:1 of LSR. From the ANOVA result, the significant factor was extraction time (p=0.0187) and was clearly showed that further increased in extraction time (25 minutes) resulted in decreased in protein concentration due to the degradation of amino acid structure at long duration of extraction time. The FTIR spectrums of the untreated and treated sample resulted in the different trend of spectrum. In the treated sample after pre-treatment process and alkaline hydrolysis, it is showed that N-H and C=O stretching peak is increased. Besides, it was confirmed that the material was correspond to amides as it consists of C=O stretch. While, from the analysis using the ICP-MS, amount of cadmium, arsenic and lead in the sample was 0.002mg/L, 0.00006mg/L and 0.262mg/L respectively after pre-treatment. It also showed that percentage decreasing of argentums, cadmium and magnesium is the highest compared to others metal which were 99%, 97.70% and 97.24% respectively. It can be concluded that EBN can be performed as an alternative source for protein.